2019
DOI: 10.1007/s11053-019-09547-9
|View full text |Cite
|
Sign up to set email alerts
|

Co-simulated Size Number: An Elegant Novel Algorithm for Identification of Multivariate Geochemical Anomalies

Abstract: Your article is protected by copyright and all rights are held exclusively by International Association for Mathematical Geosciences. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…(Figure 12), it is intuitively determined that PPMT produces satisfactory outputs in terms of reproduction of variance. However, minor deviations, such as for Fe 2 O 3 , as can be seen from this figure, are referred to the influence of conditioning data [24,50,51]. However, this tiny departure of average of variances for 100 realizations from original variance is not remarkably significant.…”
Section: Validationmentioning
confidence: 81%
“…(Figure 12), it is intuitively determined that PPMT produces satisfactory outputs in terms of reproduction of variance. However, minor deviations, such as for Fe 2 O 3 , as can be seen from this figure, are referred to the influence of conditioning data [24,50,51]. However, this tiny departure of average of variances for 100 realizations from original variance is not remarkably significant.…”
Section: Validationmentioning
confidence: 81%
“…Geostatistical tools and algorithms are widely used for modeling regionalized data and solving spatial interpolation problems for both natural and anthropogenic variables [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In this context, we decided to apply geostatistical methods to model cigarette butts and broken glass on a beach in Antofagasta, since these two items respectively represent the most common and the most dangerous forms of litter.…”
Section: Methodsmentioning
confidence: 99%
“…Typical examples of fractal and multifractal methods include the number-size model (Mandelbrot, 1983), concentration-area model, perimeter-area model (Cheng et al, 1994), spectrum-area model (Xu and Cheng, 2001), concentration-distance model (Li et al, 2003), multifractal singular value decomposition model (Li and Cheng, 2004), and singularity theory (Cheng, 2007). In recent years, even more fractal models have been proposed, e.g., the co-simulated size-number model (Madani and Carranza, 2020), global simulated size-number model (Madani and Sadeghi, 2019), concentration-distance from centroids model (Sadeghi and Cohen, 2021a), category-based fractal model (Sadeghi and Cohen, 2021b), and concentration-concentration model (Sadeghi et al, 2021). These earlier exploratory studies well demonstrated the quantitative and qualitative identification and characterization of mineralization-related spatial and frequency properties from multisource observational data sets.…”
Section: Geographic Information System-based Mineral Explorationmentioning
confidence: 99%